peningkatan Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Melalui Metode Diskusi Kelompok Kecil STUDENT TEAMS ACHIEVEMENT DIVISIONS - Ahmad Halid; Achmad Faisol; Abu Aman Siddiq Al Ghafir; Sitti Holifah Agus Niah (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2021)
Improving learning outcomes depends on the teacher teaching students. teachers must have strategies so that students can learn effectively and efficiently, and can recognize the expected goals of learning that takes place in the classroom. The focus of the research is on how to improve social studies learning outcomes through the